Assessment of bone mineral content and fracture risk: a UK prospective cohort study. (25th February 2016) - Curtis, Elizabeth; Harvey, Nicholas; D'Angelo, Stefania; Cooper, Charles; Taylor, Pat; Pearson, Gill; Cooper, Cyrus
Abstract: Background: Poor early growth is associated with reduced adult bone mineral content (BMC), but not bone mineral density (BMD). Although low BMD is a well-established risk factor for future fracture, little is known about the performance characteristics of BMC in fracture prediction. We therefore investigated the predictive value of bone area, BMC, and BMD for incident fracture in a prospective cohort of UK women. Methods: Women aged 20–80 years, recruited from four general practices in Southampton, underwent assessment by dual energy X-ray absorptiometry between 1991 and 1993. All women were then contacted in 1998–99 with a validated postal questionnaire to collect information on incident fractures and potential confounding factors including medication use. All fractures were confirmed by assessment of images and radiology reports by a research nurse. Cox proportional hazards models were used to explore the risk of incident fracture and results expressed as gradient of risk (GR) and 95% CI. Associations were adjusted for age, body-mass index, alcohol consumption, smoking, hormone replacement therapy, medications, and history of fracture. This study was approved by the Southampton Joint Ethics Committee. Findings: 674 women were recruited and 443 responded to the questionnaire. 55 women (12%) reported a fracture. In fully adjusted models, femoral neck BMC and BMD were similarly predictive of incident fracture (GR 1·64, 95% CI 1·19–2·26 [p=0·002] and 1·76, 1·19–2·60 [p=0·005], respectively). By contrast, femoral neck bone area was not associated with incident fracture (1·15, 0·88–1·50; p=0.32). Similar results were found with bone indices at the lumbar spine and whole body. Interpretation: BMC and BMD seem to predict incident fracture with similar gradients of risk, even after adjustment for body size. These findings suggest that factors in early life that are associated with total skeletal mineralisation are likely to have implications for adult fracture risk. Funding: Medical Research Council; British Heart Foundation; Arthritis Research UK; National Osteoporosis Society; International Osteoporosis Foundation; National Institute for Health Research (NIHR) Southampton Biomedical Research Centre, University of Southampton and University Hospital Southampton NHS Foundation Trust; NIHR Musculoskeletal Biomedical Research Unit, University of Oxford.